Etiology of severe short stature below −3 SDS in a screened Finnish population. Issue 5 (November 2020) - Kärkinen, Juho; Miettinen, Päivi J; Raivio, Taneli; Hero, Matti
Abstract : Objective: : To describe the etiology of severe short stature in the Helsinki University Hospital district covering a population of 1.2 million that is subject to frequent growth monitoring and screening rules during childhood. Design: : Retrospective cohort study. Methods: : We identified all subjects born 1990 or later with a height SD score <−3, after the age of 3 years, from the Helsinki University Hospital district growth database. A total of 785 subjects (376 females and 409 males) fulfilled our inclusion criteria; we reviewed their medical records and growth data and report their underlying diagnoses. Results: : A pathological cause for short stature was diagnosed in 76% of the girls and 71% of the boys ( P = NS). Syndromes were the most numerous pathological cause ( n = 160; 20%), followed by organ disorders ( n = 127; 16%), growth hormone deficiency (GHD, n = 94; 12%), SGA without catch-up growth ( n = 73; 9%), and skeletal dysplasias ( n = 57; 7%). Idiopathic short stature (ISS) was diagnosed in 210 (27%) subjects. The probability of growth-related pathology, particularly of a syndrome or skeletal dysplasia, increased with the shorter height SD score and the greater deviation from the target height. Sitting height to height SDS was increased in subjects with ISS, GHD, and SGA (all P < 0.01). Conclusions: : Height <−3 SDS after 3 years of age usually results from a pathological cause and should be thoroughly investigated in specialized health care. The chance of finding a specific etiology increased with the severity of short stature, and the mismatch with target height.